Learning to Change Together: The Social Context of Architectural Learning - MackIntosh, Lara (Common Ground Publishing, 2014)
In architectural education, learning is often structured to inform and support change to sustainable design and behaviour. The built and natural contexts in which this learning takes place are considered an important element in informing the new ways of seeing and knowing our environments, which are necessary for change. Yet the social context of learning also affects the opportunities for such transformative learning experiences. This paper discusses how this social context can influence the way in which the learner interacts with the built and natural environment and how this, in turn, can support transformation. Recent experiences of different models of learning in the US, New Zealand, and Australia are used to demonstrate the contexts—social, natural, and built—in which learning about the environment in general, and architecture specifically, takes place. An ethno-methodological approach has been taken to develop an understanding of how meaning is made through learning experiences, and how this influences behaviour. Through observations and documentation, the nature of social interchange, the role of the natural and built environments, and the effect of the learning experiences, both formal and informal, on behaviour are explored. Findings from this investigation will inform the development of a framework for architectural education.